(untitled) (Texas Journal of Multidisciplinary Studies, 2025)
This scientific article studies the effectiveness of a special training program in developing the speed qualities of female handball players. The study involved 24 athletes aged 17–20, divided into 12 control (CG) and experimental (TG) groups. A 6-week training program aimed at developing speed was developed for the experimental group. During the study, tests were conducted on 30-meter run, 4x10-meter sprint, and 20- meter run with the ball. The results showed that the athletes of the experimental group achieved significant improvements in all speed indicators (p